Las doctrinas modernas del derecho civil en la reforma del código civil peruano - Yupanqui Sandoval, Abad Enrique (2018)
The right of obligations, is a branch of civil law that studies the legal obligation, its sources, classes, effects and means of extinction. And for the sake of technological growth and making obligations grow with it. That is why in the present work a proposal is made about how the matter should be dealt with in the Peruvian civil code. For which we take, as the first argument that since 1984 to date there have been many advances in science and technology that has substantially modified the legal relationships of the Peruvian population, the same as meriting a profound modification of the Code. We should not make the mistake of thinking that this is the only time in which there are scientific or technological advances to support the legal modification since the law in general is a product of the historical advance of society. Perhaps it is the time when these advances occur faster, but that is natural and does not mean that all these changes must have an impact that manifests itself in changes to civil legislation. In addition, the argument of the advance of science and technology is not sustainable for a comprehensive reform, since most of the assumptions that are argued for this purpose, are related to very specific aspects of the Code. With this issue, extreme care should be taken, since the Code should never be a "scientific manual", since, if it were, every time there were scientific or technological advances, we would have to resort to modifying what is already modified. I think that we should tend to make the standards as wide as possible and, in this way, prolong -in the strongest way- their validity over time. The second argument put forward for the reform of the Civil Code was that in all these years of validity of the 1984 Code there had been a series of modifications to its text, the same ones that made the revision and integral adaptation of the referred one necessary. normative body. The Code has always been modified, in spite of its deficiencies, they have been rigorously complemented, both by the doctrine and by the jurisprudence. But regardless of the arguments that led us to reject those that were used in favor of the reform, there are other powerful reasons for not fully amending the 1984 Code